Molecular‐Dynamics Modeling of Nafion Membranes. Issue 1 (21st October 2022) - Sengupta, Soumyadipta; Pant, Rakesh; Venkatnathan, Arun; Lyulin, Alexey V.
Abstract: The Nafion is a commonly used polyelectrolyte membrane (PEM) in fuel cells and flow batteries. Nanocomposites of Nafion are used to enhance temperature resistance and proton conductivity. The molecular‐dynamics simulation results are reported for Nafion films of different thicknesses confined between two potential walls of variable wettability, mimicking the nanofiller surfaces. The water cluster sizes show an increase with film thickness for the high wettability cases, in agreement with SAXS experiments. The in‐plane water diffusion is considerably enhanced for the high wettability walls. The first results on the annealing effects on both structure, dynamics, and electric conductivity of the membranes are also reported. The hydrophilic channels evolution upon annealing will be discussed.